Comparative biology of the signal crayfish, Pacifastacus leniusculus (Dana), and the narrow-clawed crayfish, Astacus leptodactylus Eschscholtz - Harlioğlu, Muzaffer Mustafa (1996)
Some aspects of the biology of Pacifastacus leniusculus and Astacus leptodactylus have been compared.